PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK YANG DI MODERASI OLEH SUASANA TERHADAP KEPUASAN PELANGGAN - Sari Atul Hilaliyah (University of Merdeka Malang, 2017)
The purpose of this study is: To examine and analyze the effect of service quality on costumer satisfaction, the effect of Product quality on costumer satisfaction the effect of service quality on costumer satisfaction moderated by atmosphere, the effect of product quality on costumer satisfaction moderated by atmosphere. This type of research is explanatory research. The population are Ria Djenaka Cafe Malang costumers. Methode Sampling technique used is the purposive sampling while collecting primary data through distribution of questionnaires to undergraduate student of costumer in Ria Djenaka Cafe Malang as many as 128 costumer. In this case there are two independent variabel, service quality and product quality, one of moderated variabel is atmosphere, while the dependent variable is costumer satisfaction. The data has been collected then analyzed by using analysis of PLS (Partial Least Square).The results obtained are (1) service quality has significant effect on costumer satisfaction, (2) product quality has significant effect on costumer satisfaction, (3) atmosphere has no moderated relationship between service quality on costumer satisfaction (4) atmosphere has no moderated relationship between product quality on costumer satisfaction. DOI : https://doi.org/10.26905/jbm.v4i2.1699